Relevansi Pemikiran Al-Maturidi terhadap Penguatan Moderasi Beragama di Indonesia: Kajian Literatur - Miranda Anggraini; Sindi Junia; Vina Alia Azalira; Dita Aprilia; M. Nur Fadli; Hafizul Husni (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze Al-Maturidi’s theological thought and its relevance to strengthening religious moderation in Indonesia. Employing a qualitative approach through library research, data were collected from primary and secondary sources related to Al-Maturidi’s theology and contemporary religious moderation, then analyzed using content analysis with a descriptive-analytical approach. The findings indicate that Al-Maturidi’s thought emphasizes a harmonious balance between reason and revelation, tolerance, justice, respect for human rationality, and the firm rejection of religious extremism. These values conceptually align with the core principles of religious moderation in Indonesia, including national commitment, tolerance, non-violence, and respect for cultural diversity. The study concludes that Al-Maturidi’s thought serves as a robust theological foundation for fostering moderate, inclusive, and harmonious religious life within Indonesia’s pluralistic society. These findings are expected to provide a significant conceptual contribution to the development of moderate Islamic studies and practical strategies for strengthening religious moderation in the contemporary digital era.